RETRACTED: The Influence Of Consumer Behavior, Service Quality And Digital Marketing On Usage Decisions Pelni Passenger Ship Transfer Services - Paramitha Novianty; elwisam elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze the influence of consumer behavior, service quality and digital marketing on the decision to use PELNI passenger ship transportation services. The research method used in this study is a quantitative descriptive method with the population in this study, namely users of PELNI passenger ship transportation services. The sampling method in this study is purposive sampling. The sample in this study was 100 respondents with the criteria of passengers who used PELNI ship transportation services at least 2 (two) times during 2019, and passengers who purchased tickets at the Jakarta counter or through online applications. The data used in this study were primary data in the form of questionnaires and processed using SPSS version 23. The data analysis technique used is multiple linear regression analysis. The results showed that Consumer Behavior variables, Service Quality variables and Digital Marketing variables had a positive and significant effect on the Decision to Use PELNI passenger ship transportation services.